EFFECT OF GLUCOSE ON THE RESPONSE PAIN BABY IN PUSKESMAS GAMPING II SLEMAN YOGYAKARTA - Abdul Ghofur; Ida Mardalena (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2014)
Background. Evidence suggests that infants feel pain, and painful experiences may lead to subsequent increased pain sensitivity. Owing to concerns regarding the potential adverse effects of pharmacological interventions in newborns, effective alternatives for pain control are being sought. Pain response in infants perpapar painful invasive procedures become an important issue and needs to be given a way out, so that did not hamper the future growth and development. Efforts non-pharmacological form of glucose is a supplement that can reduce the pain response in infants. Glucose is also easy to get in the domestic order in Indonesia.This study aims to determine the effect of glucose on pain response in infants who performed immunization injection Methods.  This research method is quasi elsperiment by design "post test with equivalent groups design". While the sample in this study amounted to 64 babies which consisted of 24 infants as the treatment group, 24 infants as the control group (placeboI) and 24 infants as non-treatment group (ASI). Results. Glucose at the time of immunization injections in infants does not significantly reduce the pain response in the form of old crying in infants, with a mean value of 34.60 with a standard deviation of 57 465 and F value of 0.743. Glucose does not significantly reduce the pain response in infants immunized with injections an average value of 23.99, a standard deviation of 9329 while the value of Chi - Square significantly reduces the pain response to the pulse of infants with an average of 21.74 where the standard deviation of 13.314, with a value of Chi -   Conclusion.  The smallest pulse changes occurred  in  the breast milk, compared  with  other  groups.  This gives  the conclusion  that  breastfeeding  is a non- pharmacological analgesic that is effective in providing short-term effects on the infant imunization.